Epidemiological observations and management challenges in extrapedal mycetoma: A three-decade review of 420 cases. - Abubakr Abdalla Mohammed Alhaj; Eiman Siddig Ahmed; Abeer Hassan; Ahmed Hassan Fahal (Public Library of Science (PLoS), 2024)
Mycetoma is a serious, destructive, disfiguring chronic granulomatous inflammatory disease affecting the subcutaneous tissues that spread to involve the skin, deep tissues and bone. The disease predominately affects the limbs, and extrapedal mycetoma is rarely reported. The reported extrapedal ones are characterised by high morbidity and mortality. This communication reports on 420 patients with extrapedal mycetoma seen and managed at the Mycetoma Research Centre (MRC), University of Khartoum, between January 1991 and December 2021. In this descriptive, cross-sectional, hospital-based study, the electronic records of all mycetoma-confirmed patients seen during the study period were carefully and meticulously reviewed. The confirmed patients with extrapedal mycetoma were included in this study. The study included 420 patients with extrapedal mycetoma, 298 (70.7%) had eumycetoma, and 122 (29.3%) had actinomycetoma. There were 343 male patients (81.7%) and 77 (18.3%) females, with a male-to-female ratio of 4:1. Their ages ranged between 1.5 and 95 years, with a median of 28 years. Most of the patients were students and farmers. The majority of patients were from El Gezira, North Kordofan, and the White Nile States. Mycetoma was painful in 21%, and a family history of mycetoma was recorded in 11.5% of patients. The buttocks (37.9%) and head and neck (16.9%) were affected most. Less frequently affected sites were the trunk and back (12%) each, abdominal and chest walls (4.5%) each and loin (1%). The prominent clinical presentation findings were multiple sinuses discharging grains (55%), massive swellings (46%), and lymphadenopathy (11.5%). Less commonly observed clinical findings were local hyperhidrosis (5.3%) and dilated tortuous veins close to mycetoma lesions (0.5%). The study showed that 204 patients (48.6%) had clinical improvement in terms of decreased lesion size and healing of sinuses following medical therapy. Sixty-six patients (15.7%) had no noticeable improvement. The lesion continued progressing despite treatment in 44 patients (10.5%). In the study, 118 patients were on regular follow-up, and in this group, a cure was documented in 25 patients (21.1%) with eumycetoma and 23 (19.4%) with actinomycetoma. Post-operative recurrence among eumycetoma patients was 40%, with a 1% mortality rate. The treatment outcome was unsatisfactory, characterised by a low cure rate, high recurrence (40%) and follow-up dropout (57%) rates. This emphasises the importance of early case detection and management, objective health education programmes and thorough patient counselling to urge people to seek treatment early and reduce dropouts.